Numerical optimization with applications - Chandra, Suresh; Jayadeva; Mehra, Aparna (New Delhi: Narosa Publishing House, 2009)
Numerical Optimization with Applications provides a focused and detailed study of various numerical optimization methods and their applications in Science, Engineering and Management. Apart from discussing standard optimization methods and their traditional applications, the book includes some very recent topics like Semi-definite Programming, Second Order Cone Programming, Evolutionary Methods and Global optimization. An attempt has been made to present some modern and non-conventional applications of numerical optimization in the areas of Machine Learning, VLSI Design/ Electrical Circuits and Financial Mathematics. A distinctive feature of the book is also to provide basic MATLAB codes as building blocks for readers to develop their own codes for various algorithms discussed in the book.
References 681-690p.; Index 691-694p.
Keywords: Numerical optimization; Operational research